Long-term outcomes of 265, 737 patients hospitalised with atrial fibrillation and atrial flutter from 2008 to 2015. (14th October 2021) - Ngo, L; Woodman, R; Walters, T; Denman, R; Yang, I; Ranasinghe, I
Abstract: Background: Atrial fibrillation/atrial flutter (AF/AFL) hospitalisations are common, however, little is known about the long-term outcomes of these episodes. Objective: To examine the incidence of mortality, all-cause and cause-specific re-hospitalisations at up to 8 years after a hospitalisation for AF/AFL. Methods: Unique patients hospitalised with a primary diagnosis of AF/AFL from 2008–2015 were identified using nation-wide hospitalisation data from Australia and New Zealand. All-cause mortality was the primary outcome. Secondary endpoints included all-cause and cause-specific re-hospitalisations. Results were reported as incident rate per 100 patient-years. Results: We included 265, 737 patients (mean age 69.9±13.9y, female 45.2%, elective 28.7%). The median length of stay was 1 day (Interquartile range [IQR] 0–4 days) and the median CHA2DS2-VASc score was 2 (IQR 1–2). During the index hospitalisation, 9, 837 (3.7%) patients underwent catheter or surgical ablation and 52, 634 (19.8%) underwent cardioversion. During the median follow-up time of 3.4 years (range 0–8.0 years), 53, 669 patients died (incident rate of 5.7/100 patient-years) with a survival probability gradually decreasing from 92.8% (95% CI 92.7–92.9%) at 1-year to 65.4% (95% CI 64.9–65.8%) at 8-years post-discharge (Table 1 and Figure 1). All-cause re-hospitalisations occurred in 210, 118 patients (incident rate of 22.2/100 patient-years) with a rehospitalisation-free survival probability of 7.1% (95% CI 6.9—7.3%) at the end of follow-up. Unplanned re-hospitalisations occurred more frequently than planned episodes (incident rate of 17.2 vs. 16.6/100 patient-years respectively). AF/AFL accounted for 25.1% of all-cause re-hospitalisations (incident rate of 8.9/100 patient-years) and the probability of freedom from re-hospitalisations for AF/AFL was 55.4% (95% CI 55.0–55.8%) at 8-years. Incident rates of re-hospitalisations for catheter ablation (1.5/100 patient-years), stroke (1.6/100 patient-years), heart failure (2.7/100 patient-years), and acute myocardial infarction (1.0/100 patient-years) were low. In subgroup analyses, worse survival was observed in female patients, older age groups, patients with comorbid heart failure, hypertension, diabetes, and those who did not undergo ablation during the index hospitalisation. Conclusion: Nearly two-thirds of patients were surviving by 8-years following an AF/AFL hospitalisation with a low rate of re-hospitalisations for stroke, heart failure, and myocardial infarction. However, re-hospitalisations for recurrent atrial arrhythmia were common. Efforts to reduce re-hospitalisations, especially unplanned encounters, are required to improve patient outcomes. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): National Heart Foundation of Australia